Adult lake sturgeon (Acipenser fulvescens Rafinesque, 1817) occurrence in the Muskegon River system, a Lake Michigan drowned river mouth, USA. (29th July 2020) - Harris, Brandon S.; Ruetz, Carl R.; Ellens, Travis J.; Weinke, Anthony D.; Biddanda, Bopaiah A.
Abstract: Recent advancements in telemetry have allowed managers and researchers to conduct comprehensive studies on the movement ecology of lake sturgeon ( Acipenser fulvescens ), a species of conservation concern in most of the Laurentian Great Lakes basin. In Michigan waters of Lake Michigan, drowned river mouth systems (a protected lake‐like habitat that connects a river to lake) support 4 of 11 remaining lake sturgeon populations. One of those remnant populations is supported by the Muskegon River, a drowned river mouth system consisting of both Muskegon Lake and the Muskegon River. The objectives of this 6‐year telemetry study were to determine whether adult lake sturgeon occupied the Muskegon River system outside of the spawning season (defined as March to July), to quantify their use of the system annually, and to identify and characterize patterns in occurrence. A total of 21 adult lake sturgeon implanted with acoustic transmitters were passively monitored throughout the year during 2012–2017. Eighty‐two percent of tagged fish at large were detected ≥1 day in the Muskegon River system annually, and tagged lake sturgeon were frequently detected during both spawning and non‐spawning time periods. Residency index (i.e., no. detection days/365 days) values indicated that adult lake sturgeon were not only detected throughout the year but that they occupied the Muskegon River system for an average of 130 days each year (residency index = 0.36 ± 0.05 SE) during our most spatially intensive acoustic monitoring in 2016–2017. Additionally, 24% of tagged lake sturgeon were primary residents (i.e., residency index >0.5) of the Muskegon River system in both years. Adult lake sturgeon followed 1 of 3 patterns of occurrence based on individual detection histories, and those patterns varied temporally and by the relative amount of use (i.e., high, medium, and low). Our findings build on previous research that found drowned river mouth systems in Lake Michigan can be important nursery habitats for juvenile lake sturgeon by showing that these habitats also can be used extensively by adult lake sturgeon throughout the year.